Exploration of phosphate solubilizing bacteria from mangrove soil of Lamongan, East Java, Indonesia - FATIMAH FATIMAH; NUR AULA; SYARIFAH SALSABILA; ZAKIA ASRIFAH RAMLY; SHERINA YULIA ROSE; TINI SURTININGSIH; TRI NURHARIYATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fatimah, Aula N, Salsabila S, Ramly ZA, Rose SY, Surtiningsih T, Nurhariyati T. 2023. Exploration of phosphate solubilizing bacteria from mangrove soil of Lamongan, East Java, Indonesia. Biodiversitas 24: 1272-1278. The objective of this research was to obtain and characterize bacterial isolates from mangrove soil Lamongan, East Java, Indonesia, screen the ability of Phosphate Solubilizing Bacteria (PSB) and determine their Phosphate Solubilization Index (PSI), and identify the species of most potential PSB. Bacteria were isolated and characterized macroscopically on Nutrient Agar media. Microscopic characteristics were observed by Gram staining. Phosphate solubility test carried out using Pikovskaya Agar media. The highest PSI value bacteria was identified molecularly using 16S rRNA gene. This explorative study was analyzed descriptively. The results showed that a total of 17 isolates were obtained, of which 14 isolates were classified as Gram-positive bacteria and 3 isolates were classified as Gram-negative bacteria. All the 17 bacterial isolates showed different colony morphology. Amongst the 17 isolates, 12 of them were PSB. The TL-8 isolate was the most potential PSB, with a PSI value of 2.82. Based on the results of molecular identification with the 16S rRNA gene, TL-8 was identified as Lysinibacillus fusiformis TL-8, had 99.57% similarity with L. fusiformis strain NBRC 15717T.102 with a query cover of 100%.